Pembentukan Personal Branding pada Anak Binaan Menggunakan Konsep Diri - Eldinda Faridzi Rachmayani Sinulingga; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2023)
Every individual must have a goal in living his life, which will encourage him to develop. The life goals described by individuals must be different. In fact, every individual who has certain conditions, they have to make more effort to achieve the expected goals in life. In this case, people have unusual background stories, such as the lives of target children who get a negative stigma given by society to former target children, even though there are many former target children who want to live a much better life. Therefore, personal branding using self-concept is urgently needed for children under the Special Development Institute for Class I Children in Medan. One of the objectives of this Field Work Practice is to provide assistance to foster children which is implemented in this mini project using the Group Work at the Mezzo level, namely Assessment, Intervention Planning, Intervention, Monitoring, Evaluation, and Termination. In the process of providing assistance to clients by providing education to clients on how to build personal branding and build self-concept to clients. The results obtained from mini project have been achieved because the client now knows what their purpose in life is after their criminal term ends so they don't repeat mistakes in behavior. mini project also has a good impact not only on clients but also on other children.